Performance Measurement Systems in the Conditions of Medium and Large Companies in Slovakia - Lucie LENDELOVÁ; Petra FEJOVÁ; Viliam LENDEL (Communications of International Proceedings, 2021)
The conditions for companies to operate in today's highly competitive and rapidly changing business environment are challenging and uncertain. The key to success for companies is finding and maintaining a competitive advantage and long-term performance. Therefore, more than before, companies need to create effective strategies for their management. Due to these facts measuring and managing performance is an increasingly popular concept within strategic management. This paper deals with performance measurement issues. On the sample of selected middle and large companies is examined the performance measurement system through by an electronic questionnaire survey. There is examined for example: the length of the system implementation, the role it plays, the indicators of which it is composed, what methods, models, tools are used for systematic measurement and improvement of the system, etc. The article is divided into several basic chapters: introduction - literature review, methodology, analysis and discussion and conclusion. A list of sources is provided at the end.
Keywords: Measurement; Performance Measurement System; Companies; Slovakia.